An in vivo target mutagenesis system for multiple hosts - Yin, Dong; Pang, Qingxiao; Yuan, Yingbo; Su, Tianyuan; Liu, Mengmeng; Wang, Qian; Hou, Jin; Qi, Qingsheng (Trends in biotechnology (Regular ed.), 2025)
In vivo targeted mutagenesis technology can enable the gene of interest to generate genetic diversity within the host cell without human intervention.We developed an in vivo targeted mutagenesis system applicable to multiple hosts, effectively addressing the key gap of in vivo mutagenesis tools for unconventional hosts.This system features a longer evolution window, enabling the simultaneous evolution of multiple proteins.This system has extensive potential in unconventional host applications, facilitating more efficient enzyme engineering and metabolic optimization in industrial settings. In vivo target mutagenesis is a powerful approach to accelerate protein evolution. However, current approaches have been primarily developed in conventional organisms, limiting their capacity to evolve proteins with subtle variations across non-conventional host species. Here, we design an in vivo target mutagenesis system for multiple hosts (ITMU) utilizing the broad host-range plasmid RSF1010 replication element. The ITMU, which is based on a deaminase–helicase fusion and a primase error-prone DNA polymerase I fusion, induces all types of mutation in the target plasmid harboring the RSF1010 replicon, at a mutation rate 1.18 × 105-fold higher than that of the host genome. We show that ITMU-based in vivo continuous evolution is effective in Escherichia coli, Pseudomonas putida, Corynebacterium glutamicum, and Yarrowia lipolytica. This demonstrates that the ITMU is applicable to multiple microbial chassis and provides a viable alternative to in vivo continuous evolution systems. [Display omitted] Targeted evolution in vivo has been studied for decades; however, the extension of this technique to non-conventional hosts remains a significant challenge. This study reports an in vivo target mutagenesis system for multiple hosts (ITMU) that is applicable to both conventional and non-conventional hosts. The ITMU uses the fusion of the replication element from the broad host-range plasmid RSF1010 with DNA-modifying enzymes to achieve high frequency mutation of the target plasmid. ITMU-based in vivo continuous evolution was proved to be effective in Escherichia coli, Pseudomonas putida, Corynebacterium glutamicum, and Yarrowia lipolytica. Therefore, we assess the Technology Readiness Level (TRL) of this technology to be between 4 and 5. To facilitate the full-scale implementation of ITMU, it will be necessary to further explore and optimize DNA-modifying enzymes utilizing advanced techniques such as big data analysis and machine learning. With the recognition of the potential for non-conventional hosts to serve as the next-generation cell factory, we anticipate that ITMU will accelerate the development of novel enzymes and high-value compounds in non-conventional hosts. This study developed an in vivo targeted mutagenesis system for multiple hosts based on replication elements of broad host-range plasmids. This system is designed to accelerate the rapid evolution of proteins and metabolic pathways, further leveraging the performance advantages of unconventional hosts.